Computational investigation of African natural products as Helicobacter pylori shikimate kinase inhibitors - Hari Ram Sharma Paudel (PLoS ONE, 2026)
Helicobacter pylori is one of the most prevalent bacteria, infecting more than 40% of the world’s population. Rising antibiotic resistance has created an urgent need for the discovery of novel therapeutic agents. One of the potent drug targets for H. pylori is shikimic acid pathway, which synthesizes chorismate, an essential precursor for various aromatic compounds necessary for the survival of microorganisms. This pathway is absent in humans but its inhibition is lethal to microorganisms. In this study, shikimate kinase, which catalyzes the fifth step of the shikimic acid pathway, was targeted as a receptor. Potential inhibitors were sourced from the North African Natural Product Database (NANPDB) and the East African Natural Product Database (EANPDB). The natural products were investigated using computational tools. Molecular docking was used to screen the natural products and molecular dynamics simulation was used to assess the dynamic stability of docked protein-ligand complexes. The docking protocol was validated by heavy-atom superimposition of the docked shikimate 3-phosphate onto its co-crystallized conformation. Out of approximately 6500 compounds, six compounds with binding energy ranging from −8.73 to −10.57 kcal/mol were selected from molecular docking. Selected compounds showed stability during 200 ns molecular dynamics simulation. These compounds displayed strong prospects for experimental investigation of possible antibiotics against H. pylori .